Development of perforation-mediated modified atmosphere packaging to preserve fresh fruit and vegetable quality after harvest - Oliveira, F.A.R. (2011)
The use of perforations as a means of obtaining large size containers suitable for modified atmosphere packaging (MAP) would greatly enhance the applicability of this technology for storage and distribution of fresh and minimally processed products. General concepts of MAP, and advantages and drawbacks of using perforations to achieve it are discussed. Products for which perforated packages can be used are listed. The variables that affect this type of package are presented and the methodology for designing an adequate package is described and illustrated with the case study of shredded cabbage.